Public Private Partnership in School Resources Management: Implication for Gifted and Talented Education in Nigeria. - Lawal, Musa Ibrahim; Ahmad, Muhammad Shuaibu; Bello, Ahmad Munnira (International Journal of Educational Management, 2021)
Given market failures and equity concerns, the public sector remains an important player in providing education services, but making high-quality education accessible for all in developing countries requires innovative programs and initiatives in addition to public resources and leadership, there are ways in which the public and private sectors can join together to complement each other’s strengths in providing education services and to improve learning outcomes. This paper attempted to explain the concept of public private partnership, gifted and talented education, school resources management and how each can be applied in one another. And lastly some recommendations were given among which arePrincipals and teachers need to be trained on gifted education and needs of the gifted, the public need to be properly mobilized and enlightened on the importance of public private partnership. As they lack the knowledge of it.